FATALISME DAN EKSISTENSIALISME DALAM NASKAH DRAMA KERETA KENCANA KARYA EUGENE IONESCO TERJEMAHAN W.S. RENDRA - Setia Naka Andrian (Sasindo, 2014)
Gelimang Indonesian literature is not enough and certainly will not develop well without the strength of the criticism. Assessment of the literature was not enough if only mengacungi thumb. It is necessary to direct the investigation to analyze literary works, which is not simply to give judgment on the merits of literary works, as well as whether or not worth it. Nor only want the meaning of a literary work, not merely record the creative process alone, but more than all that. In this study, using qualitative descriptive analysis study literature as hermeneutic approach to the study of psychology. This research is expected to note the beginning and then be little to contribute material appreciation of literature, especially to the learners / students, so much loved literature that leads to the formation of attitudes and social personalities of society, as a healthy human being is a human being who will think and think, thinking to win and think that others do not lose.Keywords: Fatalism, Existentialism, Drama Script